Combination of the NanoSuit method and gold/platinum particle-based lateral flow assay for quantitative and highly sensitive diagnosis using a desktop scanning electron microscope - Kawasaki, Hideya; Suzuki, Hiromi; Maekawa, Masato; Hariyama, Takahiko (Journal of pharmaceutical and biomedical analysis, 2021)
[Display omitted] •The combination of NanoSuit and colloid metal-based LFA using an SEM produced a new diagnostic method•LFA-NanoSuit method (LNSM) can obtain clear SEM images without conduction treatment•LNSM exhibited excellent sensitivity and specificity for influenza A clinical diagnosis•LNSM can be used for POCT of several pathogenic infections as well as other diseases Owing to its simplicity and low cost, the lateral flow assay (LFA) is one of the most commonly used point-of-care diagnostic techniques, despite its low sensitivity and poor quantification. Here, we report a newly developed LFA-NanoSuit method (LNSM) combined with a desktop scanning electron microscope (SEM) for the direct observation of immunocomplexes labeled with a colloidal metal instead of signal enhancement strategies, such as using color, electrochemical signals, silver enhancement, magnetic properties, luminescent, and surface-enhanced Raman spectroscopy (SERS). The proposed LNSM suppresses cellulose deformity, thereby allowing the acquisition of high-resolution images of gold/platinum-labeled immunocomplexed pathogens such as influenza A, without conductive treatment as in conventional SEM. Electron microscopy-based diagnosis of influenza A exhibited 94 % clinical sensitivity (29/31; 95 % confidence interval [CI]: 79.3–98.2 %) and 100 % clinical specificity (95 % CI: 98.1–100 %), which was more sensitive (71.4 %) than visual detection (14.3 %), especially in the lower influenza A-RNA copy number group. The detection ability of our method was nearly comparable to that of real-time reverse transcription-PCR. This is the first report on the diagnosis of clinical diseases using LFA equipped with a desktop SEM. This simple and highly sensitive quantitative analysis method involving LFA can be used to diagnose various diseases in humans and livestock, including highly infectious diseases such as COVID-19.